A Cognitive Linguistics Application for Second Language Pedagogy: The English Preposition Tutor. Issue 2 (11th January 2018) - Wong, Man Ho Ivy; Zhao, Helen; MacWhinney, Brian
Abstract: This study investigated the effects of teaching English prepositions using schematic diagrams inspired by cognitive linguistics in a computer‐based tutorial system called the English Preposition Tutor. Training was designed based on the theoretical framework of the Competition Model and a cognitive linguistic analysis of prepositions. Sixty‐four Cantonese‐speaking intermediate learners of English were trained using a sentence–picture matching task. They received one of the three types of feedback: schematic diagram feedback, metalinguistic rule feedback, or correctness feedback. Only the schematic diagram feedback group was exposed to chaining between spatial senses and nonspatial senses. Results showed that instruction was effective in all three feedback groups, as measured by a cloze test and a translation test. In the translation test, the group receiving schematic diagram feedback outperformed the correctness feedback group. The effects of the three feedback conditions were not significantly different in the cloze test.